2017
DOI: 10.1016/j.ijcard.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine for primary prevention of atrial fibrillation after open-heart surgery: Systematic review and meta-analysis

Abstract: Colchicine demonstrated superior efficacy versus usual care for prevention of atrial fibrillation after cardiac surgery. Moreover, colchicine treatment was associated with shorter hospital stays. These benefits outweigh increased risk of adverse drug-related effects; although further work is needed to minimize gastrointestinal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 42 publications
(54 reference statements)
1
56
0
5
Order By: Relevance
“…Arrhythmias accounted for about one in five readmissions. There is continued data to suggest that prophylactic colchicine may reduce the incidence of postoperative atrial fibrillation, yet this practice has not been widely adopted and merits further study in light of the potential impact on patient outcomes and readmission prevention …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrhythmias accounted for about one in five readmissions. There is continued data to suggest that prophylactic colchicine may reduce the incidence of postoperative atrial fibrillation, yet this practice has not been widely adopted and merits further study in light of the potential impact on patient outcomes and readmission prevention …”
Section: Discussionmentioning
confidence: 99%
“…There is continued data to suggest that prophylactic colchicine may reduce the incidence of postoperative atrial fibrillation, yet this practice has not been widely adopted and merits further study in light of the potential impact on patient outcomes and readmission prevention. 27 There is an unfortunate gap in the literature regarding evidencebased interventions to reduce readmissions following cardiac surgery. 28 Early efforts to improve the management of CHF patients, based largely on improving care coordination, may provide a model for cardiac surgical patients.…”
Section: Preoperative Predictors Of Readmissionmentioning
confidence: 99%
“…This result might suggest a higher association between EATa and AF (Batal et al, ) because the neutrophil to lymphocyte ratio was an AF recurrence predictor after ablation or new onset AF after CABG (Gibson et al, ; Li, Cui, Ma, Ma, & Li, ). Along this line, colchicine, which reduces neutrophils' activity (Paschke et al, ), was shown to be efficient for AF prevention after cardiac surgery (Lennerz, Barman, Tantawy, Sopher, & Whittaker, ). Although colchicine might cause leukopenia in a dose‐independent manner (Dixon & Wall, ), leukocytes deficiency was associated with worse clinical outcomes in patients who underwent heart surgery (Cabrera et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a meta-analysis by Lennerz et al 19 focused on 1412 patients undergoing cardiac surgery. The primary end point was POAF after treatment with colchicine; secondary end points included hospitalization length and side effects after colchicine treatment.…”
Section: Meta-analysesmentioning
confidence: 99%